Development of a Quantitative Assessment System for Upper Limb Motor Disorder in Occupational Therapy - Nor Azmi Ab Patar, Mohd; Lee, Hokyoo; Mahmud, Jamaluddin; Patar, Azim (International Journal of Engineering and Technology, 2018)
Many stroke patients nowadays prefer home rehabilitation, which limits their access to proper rehabilitation equipment, treatment, or assessment by therapists. Currently, the rehabilitation programs neglect to maintain a patient’s motivation in doing rehabilitation exercises. The programs also lack a monitoring system to evaluate the patients’ performance quantitatively although this is the most crucial element in rehabilitation. In order to solve these problems, we have developed a novel measurement system for upper limb motor disorder rehabilitation using an optical sensor. This system consists of an optical sensor device, a personal computer and a computerized calculated program for upper limb locus position. The optical sensor detects the user’s motions and calculates position and velocity. The sanding block position, velocity and the motion length of the block during the sanding task of five subjects with motor function disorder were measured. The accuracy of the trajectories was similar in all the actual measured subjects. These outcomes have a potential for the development of rehabilitation training programs and evaluation methods.